2016
DOI: 10.5194/amt-9-1431-2016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of potential interferences in the detection of atmospheric RO<sub><i>x</i></sub> radicals by laser-induced fluorescence under dark conditions

Abstract: Abstract. Direct detection of highly reactive, atmospheric hydroxyl radicals (OH) is widely accomplished by laserinduced fluorescence (LIF) instruments. The technique is also suitable for the indirect measurement of HO 2 and RO 2 peroxy radicals by chemical conversion to OH. It requires sampling of ambient air into a low-pressure cell, where OH fluorescence is detected after excitation by 308 nm laser radiation. Although the residence time of air inside the fluorescence cell is typically only on the order of m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
63
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 48 publications
13
63
6
Order By: Relevance
“…Similarly, two FAGE groups have reported interferences in their OH measurements made using wavelength modulation in the presence of ambient levels of ozone and alkenes (Mao et al, 2012;Novelli et al, 2014), 25 whilst, in contrast, good agreement between OH measurements made using FAGE and differential optical absorption spectroscopy (DOAS) during chamber measurements suggests minimal interferences in the presence of ozone and alkenes for a third FAGE instrument (Fuchs et al, 2013). This lack of interference was further corroborated in recent laboratory tests (Fuchs et al, 2016) although an artefact signal under dark conditions (deriving from NO3 in the presence of H2O) was identified. These potential artefacts make it difficult to identify trends in earlier model-measurement comparisons and to assess 30 how well the models are performing under a range of chemical conditions.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Similarly, two FAGE groups have reported interferences in their OH measurements made using wavelength modulation in the presence of ambient levels of ozone and alkenes (Mao et al, 2012;Novelli et al, 2014), 25 whilst, in contrast, good agreement between OH measurements made using FAGE and differential optical absorption spectroscopy (DOAS) during chamber measurements suggests minimal interferences in the presence of ozone and alkenes for a third FAGE instrument (Fuchs et al, 2013). This lack of interference was further corroborated in recent laboratory tests (Fuchs et al, 2016) although an artefact signal under dark conditions (deriving from NO3 in the presence of H2O) was identified. These potential artefacts make it difficult to identify trends in earlier model-measurement comparisons and to assess 30 how well the models are performing under a range of chemical conditions.…”
Section: Introductionmentioning
confidence: 65%
“…Such an artefact has been observed in other FAGE systems (Griffith et al, 2016;Fuchs et al, 2016;Tan et al, 2017), and although the reported magnitude of the interference is variable for different systems, the signal scales linearly with both O3 and H2O and displays a quadratic dependence with laser power. The following correction has been applied to the OH data presented here which corresponds to 5.2×10 5 molecule cm -3 of OH at 50 ppbv O3, 2% H2O and 10 mW laser power (determined after the campaign but under the 10 same experimental conditions):…”
Section: Ohmentioning
confidence: 90%
See 1 more Smart Citation
“…They found that, under reactant concentrations that were orders of magnitude greater than ambient, the ozonolysis of propene, α-pinene, limonene, and isoprene produced a detectable interference in their instrument that increased with the turnover rate of the reaction. Extrapolating their results to ambient concentrations of ozone and alkenes would suggest that the ozonolysis of these compounds would not produce a detectable interference in their instrument under ambient conditions (Fuchs et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the large pressure and temperature gradients which occur as the sample enters the FAGE detection cell, the dissociation pathway of these intermediate species may be favored, leading to additional OH production. Recently, Fuchs et al (2016) performed laboratory and chamber experiments to determine whether the ozonolysis of alkenes produced an OH artifact in their LIF-FAGE instrument. They found that, under reactant concentrations that were orders of magnitude greater than ambient, the ozonolysis of propene, α-pinene, limonene, and isoprene produced a detectable interference in their instrument that increased with the turnover rate of the reaction.…”
Section: Introductionmentioning
confidence: 99%